Anti-helminthic drugs in recurrent apthous stomatitis: A short review - Shilpa Sharma; Fareedi Mukram Ali; Kedar Saraf; Anupama Mudhol (Journal of Pharmacy and Bioallied Sciences, 2014)
Recurrent aphthous stomatitis (RAS) is a common mucosal condition producing painful ulcerations in the oral cavity and considerable clinical morbidity. The etiology remains obscure, though local trauma, psychologic stress, hematinic deficiencies and immune dysregulation have been implicated. Though the primary goals of therapy are symptomatic relief of pain, the clinicians are aiming toward reducing the frequency, duration, number of ulcerations and increasing ulcer free periods with systemic drug therapy if topical medications appear ineffective. Levamisole, an antihelminthic drug has been tried with promising results in patients with severe RAS providing long-term benefits.